2018
DOI: 10.1177/1010539518772191
|View full text |Cite|
|
Sign up to set email alerts
|

Generativity Among Elderly in a Rural Area of Maharashtra, India: Correlates and Relationship With Quality of Life Approved

Abstract: Generativity, "a concern for others and a need to contribute something to the next generation," is a dimension of successful aging in and of itself, but also predicts other positive health outcomes. We examine its manifestations and correlates among elderly in rural India and assess the association between generativity and quality of life (QoL). Three hundred and forty-eight rural Indian elderly completed an interviewer-assisted questionnaire assessing generativity, QoL, and other personal and familial factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
4
0
2
Order By: Relevance
“…For men, the health benefits of generativity were predominantly influenced by human capital, but among women, it was social capital that facilitated the health benefits through generativity. Such findings support the theoretical underpinning that pathways to health are shaped by sociocultural expectations [28,30], and these vary by gender. As men tend to make contributions in areas related to material-provision or skill-transfer whereas women tend to be generative via activities such as caregiving and offering emotional support [41], different capital drivers may facilitate generativity, leading to differential health consequences between men and women.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For men, the health benefits of generativity were predominantly influenced by human capital, but among women, it was social capital that facilitated the health benefits through generativity. Such findings support the theoretical underpinning that pathways to health are shaped by sociocultural expectations [28,30], and these vary by gender. As men tend to make contributions in areas related to material-provision or skill-transfer whereas women tend to be generative via activities such as caregiving and offering emotional support [41], different capital drivers may facilitate generativity, leading to differential health consequences between men and women.…”
Section: Discussionsupporting
confidence: 73%
“…There have been calls for more studies to explore the role of social context in the realization of generativity, given the influence of social and cultural environments in dictating normative expectations and opportunities for generativity, its driving factors, and outcomes [18]. Among all the sociocultural influences in the development of generativity, gender differences are particularly salient because of the differential expectations and norms society places on men and women in their formative years, which eventually lead to variations in their expression of generativity [28]. Although gender norms evolve over time, studies, i.e., [29,30] have generally supported the notions that women, as girls, are more likely to receive training in areas related to family welfare (e.g., offer care to family members) or are expected to have a nurturing role.…”
Section: Gendered Pathway To Generativitymentioning
confidence: 99%
“…Research among 348 older adults across 10 villages in India found that overall generativity was slightly higher among men than women. The same study demonstrated that high generativity further contributes to the higher quality of life and SWB of participants (Østbye et al, 2018). On the other hand, Sagara and Ito (2017) in their article stated that generativity can be looked at in two dimensions, namely the consciousness toward generativity and the willingness to contribute.…”
Section: Discussionmentioning
confidence: 85%
“…The Loyola Generativity Scale (LGS) is a self-reported scale developed by McAdams and de St Aubin (1992) to assess Erikson's (1950) theory of generativity, which encompasses measures of generative beliefs, namely the desire to pass on knowledge, skills, and a legacy to the next generation, to care and take responsibility for others, and to take part in activities that will have a lasting impact on one's community or society. The LGS has been validated across various populations and contexts and has been used in previous research among the elderly in South Asia (Østbye et al, 2018; Rahmaniah & Krisnatuti, 2016). The LGS contains 20 items such as “I try to pass along the knowledge I have gained through my experiences” and “I think that I will be remembered for a long time after I die.” Response options utilize a four-point Likert scale, ranging from 0 = “never applies to you” to 4 = “applies to you very often or nearly always,” with six items being negatively worded and reverse coded.…”
Section: Methodsmentioning
confidence: 99%
“…There is a growing body of literature examining the positive implications of generativity for older adults. Generative beliefs have been linked to a positive experience of aging, life satisfaction, and well-being for older adults (Cheng, 2009;Østbye et al, 2018;Thiele & Whelan, 2008;Ying et al, 2020). Moreover, the Midlife in the United States Study demonstrated that generativity lowered older adults' risk of experiencing functional limitations and mortality over a 10-year period (Gruenewald et al, 2012).…”
mentioning
confidence: 99%